BIOCHEMICAL EFFECTS OF LYCOPENE ON BLOOD GLUCOSE IN HIGH SUCROSE DIET FED MALE WISTER ALBINO RATS.: JPUMHS;2025:15:01,92 98.http://doi.org/10.46536/jpumhs/2025/15.01.601 - Hafsa Usman Sheikh1, Salauhdiin Shaikh2, Mubina Laghari3, Farheen Malik4, Afsheen5, Rutesh Kumar6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2025)
OBJECTIVE: To evaluate the Biochemical effects of lycopene on blood glucose in high sucrose diet fed male wister albino rats. METHODS: An experimental research, spanning six months and carried out at LUMHS Jamshoro, utilized 60 adult male Albino Wistar rats, which were randomly assigned to four groups. Group A received 0.9% normal saline, while Group B, serving as the positive control, was given a sucrose-rich diet with no additional treatment. Experimental Groups C and D were administered the same sucrose diet along with lycopene at doses of 40 mg/kg and 60 mg/kg body weight, respectively, over a 28-day period. Lycopene was delivered daily through intragastric intubation. After the treatment phase, blood samples were collected via cardiac puncture, and serum was separated for biochemical testing to assess blood glucose levels. Statistical evaluation was carried out using SPSS software version 23.0. RESULTS: After four weeks, Group A (negative control) had a mean glucose level of 135.8 mg/dL, while Group B (positive control) showed a significantly higher level of 206.8 mg/dL (P=0.0001). Lycopene-treated Groups C and D exhibited reduced glucose levels of 177.1 mg/dL and 152.4 mg/dL, respectively, showed a statistically significant decrease compared to the positive control (P=0.0001). CONCLUSION: The study revealed that lycopene significantly lowered serum glucose levels, suggesting its potential as a safe, accessible, cost effective, and community-friendly natural option for managing hyperglycemia.